2021
DOI: 10.1111/ppe.12841
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus real‐time PCR may potentially reduce intrapartum maternal antibiotic treatment

Abstract: Background Protocols for preventing early‐onset group B streptococcal (GBS) neonatal infection may result in unnecessary antibiotics administration. Real‐time polymerase chain reaction (PCR) can provide a result within 30–60 min and has been found to be specific and sensitive for defining intrapartum GBS status. Objective To evaluate whether implementation of GBS fast real‐time PCR to all women who require GBS prophylaxis may reduce the use of maternal prophylactic antibiotics. Methods This prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…While this life-saving therapy remarkably improved the quality of life of people living with HIV, it means that many newborns are exposed to ART in utero, and the potential risks and benefits of this maternal treatment on birth outcomes and longer-term offspring health are still unclear. Three articles [4][5][6] in this special issue of Paediatric and Perinatal Epidemiology illustrate the importance of prospective studies from LMICs on infection during pregnancy, and on the impact of new strategies to improve birth outcomes and neonatal health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While this life-saving therapy remarkably improved the quality of life of people living with HIV, it means that many newborns are exposed to ART in utero, and the potential risks and benefits of this maternal treatment on birth outcomes and longer-term offspring health are still unclear. Three articles [4][5][6] in this special issue of Paediatric and Perinatal Epidemiology illustrate the importance of prospective studies from LMICs on infection during pregnancy, and on the impact of new strategies to improve birth outcomes and neonatal health.…”
mentioning
confidence: 99%
“…Despite global advocacy to highlight the GBS burden, research gaps remain and implementation of preventive strategies in LMICs is urgently needed. In another article in this special issue, by evaluating whether diagnosis of maternal GBS colonisation could be done by real‐time polymerase chain reaction (PCR) at the time of delivery, Kugelman and colleagues 6 concluded that PCR had good sensitivity and specificity compared to culture to detect GBS. They suggested that the need for maternal prophylactic antibiotics could be substantially reduced by using this strategy compared with antepartum universal culture screening or intrapartum risk‐factor assessment.…”
mentioning
confidence: 99%
“…However, such preventive measures must be applied efficiently and effectively. Kugelman and colleagues 12 evaluated the potential use of real‐time PCR in place of universal screening at 37 weeks of pregnancy to reduce the use of prophylactic antibiotics against GBS disease. The authors show that in many cases, universal screening results in unnecessary antibiotic use for the prevention of GBS—important for tailoring our screening measures.…”
Section: Application To Maternal and Infant Health Promotionmentioning
confidence: 99%